An inclined detector geometry for improved X‐ray total scattering measurements. Issue 2 (1st April 2023) - Burns, Nicholas; Rahemtulla, Aly; Annett, Scott; Moreno, Beatriz; Kycia, Stefan
Abstract : An inclined geometry is investigated for X‐ray total scattering measurements using a digital flat‐panel area detector. The inclined geometry enables acquisition of higher quality data for simultaneous Rietveld refinement and total scattering studies, yielding structural information on the short‐, medium‐ and long‐range orders from one single measurement. Abstract : X‐ray total scattering measurements are implemented using a digital flat‐panel area detector in an inclined geometry and compared with the traditional geometry. The traditional geometry is defined here by the incident X‐ray beam impinging on and normal to the center‐most pixel of a detector. The inclined geometry is defined here by a detector at a pitch angle α, set to 15° in this case, bisected by the vertical scattering plane. The detector is positioned such that the incident X‐ray beam strikes the pixels along the bottom edge and 90° scattered X‐rays impinge on the pixels along the top edge. The geometric attributes of the inclined geometry translate into multiple benefits, such as an extension of the measurable scattering range to 90°, a 47% increase in the accessible magnitudes of the reciprocal‐space vector Q and a leveling of the dynamic range in the measured total scattering pattern. As a result, a sixfold improvement in signal‐to‐noise ratios is observed at higher scattering angles, enabling up to a 36‐fold reduction in acquisition time. Additionally, the extent of applied modification functions is reduced, decreasing the magnitude of termination ripples and improving the real‐space resolution of the pair distribution function G ( r ). Taken all together, these factors indicate that the inclined geometry produces higher quality data than the traditional geometry, usable for simultaneous Rietveld refinement and total scattering studies.